Insider/Outsider: A Feminist Introspective on Epistemology and Transnational Research - Motapanyane, J. Maki (Atlantis, 2010)
This article reflects on the methodological politics of transnational research from an interdisciplinary feminist perspective. A doctoral study focused on South Africa and carried out in affiliation with a Canadian university serves as the point of departure in a wider discussion of ethics and collaboration in cross-cultural and transnational research endeavors.